Investigation of structural and luminescence properties of BaMgAl10O17:Eu2+ phosphor synthesized using auto combustion method. (2021) - Chandar Rao, P.; Ravinder, G.; Jyothsna, S.; Manjula, G.; Raju, B.; Sreelatha, C.J.
Abstract: In plasma display panel, Eu 2+ doped BaMgAl10 O17 :Eu 2+ (BAM: Eu 2+ ) Barium Magnesium Aluminate phosphor have been traditionally adapted as a blue emitting element in many displays owing availability and high (>98%) quantum efficiency. (BAM) phosphor was synthesized in two steps using auto-combustion method followed by sintering in reducing atmosphere. The X-ray diffraction examination confirmed that the crystalline phase of BAM nanophosphor as hexagonal structure. The SEM observation revealed a sharp stone like morphology for the as-prepared nanophosphor. Detailed investigation of photoluminescence has done in the current paper. The results are promising and suggest that the BAM nanophosphor is highly useful in enhancing the color purity in the modern displays.